AlAfnan Taxonomy of Educational Objectives : Unifying Domains with AI, ESD Goals, Assessment Methods, and Interdisciplinary Approaches to Teaching - AlAfnan, Mohammad Awad, (Educational Research E-Books Online, Collection 2026., 2025)
Discover a groundbreaking approach to education with AlAfnan's Taxonomy of Educational Objectives . This book redefines traditional learning frameworks by integrating artificial intelligence, sustainability goals, and interdisciplinary teaching. It addresses key challenges in modern education, such as adapting assessment strategies, fostering critical thinking, and incorporating AI-driven learning. Unlike conventional taxonomies, this model unifies cognitive, affective, and psychomotor domains, ensuring holistic student development. Through case studies and practical applications, you will learn how to implement innovative teaching strategies that enhance engagement and learning outcomes. Essential for educators, researchers, and policymakers, this Taxonomy provides the tools to transform education for the 21st century.